Prevalence and determinants of the dual burden of malnutrition at the household level in Puna and Quebrada of Humahuaca, Jujuy, Argentina - Bassett, Maria Natalia (2014)
Objective: The objective of the present study was to identify households in which overweight and underweight coexisted (dual burden of malnutrition) and explore the factors that could be contributing to the dual burden of malnutrition at the household level in this population. Study design: Cross-sectional nutritional survey. Methods: After applying the exclusion criteria, 136 households were included. Mothers were classified as normal weight or overweight/obese based on body mass index (BMI) cut-off points and children and adolescents were classified as stunted or not based on height-for-age z-score. Households with an obese mother and a stunted children or adolescent were categorized as dual burden households. Results: The prevalence of dual burden household was 12%. Compared with other households, dual burden households tended to have more people living in the house, and the educational level of the head of household was lower. Individuals living in dual burden households showed overall lower energy intakes and were more likely to have inadequate intakes of calcium and iron. Conclusions: The nutrition transition in this community might be one of the leading causes of the observed dual burden of malnutrition. The results presented here indicate the need to consider whether programs that focus on only one type of nutritional problem come might actually exacerbate the other.